Alkaloids from transannular iodoaminations - Brock, E (2012)
This thesis is concerned with the development of transannular iodoamination methodology for the synthesis of pyrrolizidine, indolizidine and tropane alkaloids. Chapter 1 introduces the concept of a ‘transannular cyclisation’ and outlines the utility of such cyclisations in the synthesis of a range of [x.y.z]-azabicyclic alkaloids. Chapter 2 describes the development of a three step lithium amide conjugate addition, ring-closing metathesis and transannular iodoamination protocol for the preparation of the pyrrolizidine scaffold ([3.3.0]-azabicycle). Cyclisation of a hexahydroazocine occurs with concomitant N-debenzylation to give a single diastereoisomer of the corresponding C(7)-iodopyrrolizidine product, which is then elaborated to the known pyrrolizidine, (−)-7a-epi-hyacinthacine A1. Chapter 3 delineates an extension of the methodology described in Chapter 2, and an investigation into accessing alternate diastereoisomeric pyrrolizidine scaffolds via the transannular iodoamination process. These studies culminate in the synthesis of two pyrrolizidine alkaloids, (−)-hyacinthacine A1 and (−)-hyacinthacine A2. Chapter 4 details investigations into the further elaboration of the C(7)-iodopyrrolizidine scaffold synthesised in Chapter 2. A nucleophilic displacement reaction with azide leads to the synthesis of novel 7-deoxy-7-aminoalexine analogues, whilst radical-mediated substitution of the iodide by oxygen allows the synthesis and isolation of the pyrrolizidine alkaloid (−)-1-epi-alexine. Chapter 5 outlines the development of the transannular iodoamination reaction to facilitate the synthesis of the tropane architecture ([3.2.1]-azabicycle). A tandem lithium amide conjugate addition and aldol reaction sequence is followed by ring-closing metathesis to give the required aminocycloheptene. Subsequent treatment with iodine results in transannular cyclisation to give a single iodotropane product which, following elaboration culminates in the synthesis of (+)-pseudococaine. Chapter 6 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2, 3, 4 and 5.